Case Report Chest Non-contrast ct-scan findings and follow up a patient suspected covid-19 infection - Ngesti Chintia Dewi; Sutaryanu Dermoredjo Dermoredjo (Faculty of Medicine Universitas Kristen Duta Wacana, 2021)
Background Covid-19 is an infection caused by SARS-CoV-2. Chest X-Ray (CXR) examination doesn’t show the radiographiccharacteristic of Covid-19 infection. Thorax CT-Scan is the gold standard imaging for pneumonia Covid-19 infection.Aim The purpose of this report is to describe a case of bronchopneumonia in a male patient aged 48 years old at Bethesda Hospital Yogyakarta during the Covid-19 pandemic.Case Description A 48 years old male patient came to the Bethesda Hospital in Yogyakarta with a complaint of fever 1 week before being hospitalized. The patient also complained of cough, sore throat, rhinorrhea, shortness of breath, malaise, and decreased appetite. The rapid test result shows SARS-CoV2 IgM and IgG (+), PCR swab Covid-19 results (+). Bronchopneumonia was concluded by CXR examination and chest non-contrast CT-Scan showed Covid-19 infection imaging characteristics. Later on, the patient showed clinical and radiological improvement.Conclusion Covid-19 is an infection caused by the SARS-CoV-2. Common symptoms are fever, cough, sore throat, shortness of breath, and malaise. CXR examinations on patients with Covid-19 infection show images of pneumonia, in this case, bronchopneumonia was concluded. CT-scan shows characteristic imaging of Covid-19 infection can support the decision on regular ward admission versus ICU and for follow-up in regular ward admission.